Antimalarial Activity of Piperine. (6th December 2018) - Thiengsusuk, Artitaya; Muhamad, Phunuch; Chaijaroenkul, Wanna; Na-Bangchang, Kesara
Abstract : Malaria remains a public health problem in tropical and subtropical regions. Resistance of Plasmodium falciparum to artemisinins in Southeast Asia is a great concern for disease control and research on discovery and development of new alternative antimalarial drugs is urgently required. In a previous study, the fruit of Piper chaba Hunt. was demonstrated to exhibit promising antimalarial activity against the asexual stage of 3D7 (chloroquine-sensitive) and K1 (chloroquine-resistant) P. falciparum clones. The aim of the present study was to further investigate the antimalarial activity of piperine, the major isolated constituent of Piper chaba Hunt. fruits against both P. falciparum clones. The antimalarial activity was determined using SYBR green-I-based assay and morphological change was observed under the light microscope with Giemsa staining. The median IC50 (concentration that inhibits parasite growth by 50%) values of piperine against 3D7 and K1 P. falciparum were 111.5 and 59 μ M, respectively. A marked change in parasite morphology was observed within 48 hours of piperine exposure. Results of real-time PCR showed no effect of piperine on modulating the expression of the three genes associated with antimalarial drug resistance in P. falciparum, i.e ., pfcrt, pfmdr1, and pfmrp1 . Piperine could be a promising candidate for further development as an antimalarial drug based on its antimalarial potency and low risk of resistance development.